The Effects of Effluents’ Discharge from Some Paint Industries on Soil’s Physicochemical Properties and Bioattenuation of Polluted Soil - Chukwuma, Okafor Ugochukwu; Uchenna, Orji Michael; Ogonna, Umeh Sophina; Chinedu, Onuorah Samuel (Tecno Scientifica Publishing, 2022)
Rapid population growth resulting in industrial proliferation and urbanization has led to the rapid increase in pollution of the environment. Paint industries in urban areas mostly channel their wastewater into streams and on land, which results in the pollution of the receiving environment. This study aims to determine the impact of effluent discharges from paint industries on the soils’ physicochemical properties and the clean-up of the polluted soil through monitored natural attenuation. Composite samples of paint-effluents and soils were collected from paint industries. Their bioattenuation levels and changes in their physicochemical properties were monitored over a six-month period. Fungal isolates from the effluents include Saccharomyces cerevisiae (20%), Rhodotorula species (15%), Aspergillus niger (25%), Aspergillus flavus (15%), and Penicillum notatum (25%), while the bacterial isolates include Staphylococcus aureus (30%), Bacillus sp. (20%), Klebsiella sp.(15%), Escherichia coli (15%), Salmonella sp. (10%), and Staphylococcus species (10%). The effluents showed slightly alkaline pH values while the soils showed slightly acidic pH values. There were significant reductions in the heavy metal contents of the effluent polluted soils as remediation time increased, thus reducing the toxicity of such soil environments. Monitored natural-attenuation methods should be employed and improved as a means of reducing the toxicity of effluents on the environment since they are cheap and effective compared to other methods.